Biological functions of Piriformospora indica and its action mechanisms - SONG Feng-ming; MAO Ke-ke; WU Cheng-cheng; LI Da-yong (浙江大学学报. 农业与生命科学版, 2011)
Piriformospora indica is one of recently found endophytic fungus in plants. This minireview summarizes the characteristics of P. indica, mutualistic interactions between P. indica and its host plants, biological functions and its action mechanisms of P. indica in plant growth/development and tolerance against biotic and abiotic stresses.